Factors in job characteristics influence employees' motivation in administration unit of Chief Minister Department Malacca / Nor Hazira Sahari - Sahari, Nor Hazira (Faculty of Office Management and Technology, 2013)
Purpose - The purpose of this study is to examine the relationships between the factors in job characteristics with the employees' motivation and to examine the factors in job characteristics that influencing employees' motivation. Methodology - The study used stratified random sampling to select the sample size of respondents from employees in Units of Administration Services at Chief Minister Department of Malacca. Data were collected on a structured questionnaire containing some demographic background of respondents, factors in job characteristics and employees' motivation. Then the data analyzed using descriptive statistical analysis, coefficient of reliability analysis and Pearson Correlation Coefficient analysis. Findings - Consistent with previous studies related to relationship between factors in job characteristics and employees' motivation, the study showed that all the factors in job characteristics (skill variety, task identity, task significance, job autonomy and feedback) have a positive significant relationship with employees' motivation. Conclusion - The research has proven that the factors in job characteristics have positive relationship with employees' motivation. However, factor in job characteristics that has the highest relationship with employees' motivation is skill variety. As a conclusion, there is positive relationship between factors in job characteristics with employees' motivation. Recommendation - It can be recommended that, for the future studies to be conducted at private sector in Malaysia, since, the researcher conducts the study at public sector area.